LEGAL ANALYSIS OF SYSTEM IMPLEMENTATION REVIEWED EVIDENCE IN CRIMINAL ACTIONS MONEY LAUNDERING - Dwiki Rafli Pasha; Dani Sintara (Fox Justi : Jurnal Ilmu Hukum, 2023)
Application is an act of practicing a theory, method, to achieve a certain goal. I n this case the intended application is how to apply the reverse verification system to money iaundering crimes. In general, money iaundering has been classified as a crime and classified as a white-collar crime, and is considered an extraordinary crime or even a serious crime because it has a different and more dangerous modus operandi than conventional crimes known in law. crime in Indonesia. in eradicating money iaundering, the most i mportant thing is ihe process of proof. The process of proving money iaundering is different from examining criminal cases in general, because money laundering is an extraordinary crime. extraordinary efforts as well (extraordinary enforcement). One form of ihis extraordinary effort is i n ihe context of proving money iaundering cases i n court using a limited and balanced mechanism of reversing ihe burden of proof or reversed proof. In this study, normative legal research methods were used, namely legal research carried out by examining literature or secondary data as a basis for research by conducting a search of regulations and literature related io ihe problem io be studied.